A Case of Laparoscopic Resection for Carcinoma of the Gastric Remnant following Proximal Gastrectomy Reconstructed with Jejunal Interposition - Kazuhito Yajima; Yoshiaki Iwasaki; Ken Yuu; Ryouki Oohinata; Misato Amaki; Yoshinori Kohira; Souichiro Natsume; Satoshi Ishiyama; Keiichi Takahashi (Case Reports in Surgery)
A 72-year-old Japanese man had a history of proximal gastrectomy for early gastric cancer located in the upper third of the stomach in 2007. Our usual treatment strategy for early gastric cancer in the upper third of the stomach in 2007 was open proximal gastrectomy reconstructing by jejunal interposition with a 10 cm single loop. Upper gastrointestinal fiberscopy for annual follow-up revealed a type 0-IIc-shaped tumor with ulcer scar, 4.0 cm in size, located in the gastric remnant near the jejunogastrostomy. A clinical diagnosis of cancer of the gastric remnant, clinical T1b(SM)N0M0, Stage IA, following the proximal gastrectomy was made and a laparoscopic approach was selected because of the cancer’s early stage. Remnant total gastrectomy with D1 plus lymphadenectomy was carried out with five ports by a pneumoperitoneal method. Complete resection of the reconstructed jejunum was undergone along with the jejunal mesentery. Reconstruction by the Roux-en-Y method via the antecolic route was selected. Total operative time was 395 min and blood loss was 40 mL. Our patient was the first successful case of resection for carcinoma of the gastric remnant following proximal gastrectomy reconstructed with jejunal interposition in a laparoscopic approach.